Research of features of manifestation of junior schoolchild’s egotism in communication with peers - Radul, Iryna Hennadiivna; Hundarenko, Olena Volodymyrivna; Kowalczyk, Marlena Miroslawa (Insight: the psychological dimensions of society, 2020)
The purpose is to study empirically the level of egotismof junior schoolchild as a speech form of personalegocentrism during his/her interaction with peers. Methods. Theoretical analysis and systematizationof scientific resources on the problemof research was used in the study of egotism asa speech form of personal egocentrism. “Methodsof studying egotism” has been used in order tostudy the phenomenon of egotism of dialogic speechand “Methods of studying egocentrism during interaction”by T. Pashukova and open uninvolved observationhave been used in order to establish the relationshipbetween egotism and the dominant formof personal egocentrism. Results. Personal egocentrismreflects a person's position in relation tothe world around him/her, and is characterized bya focus on his/her position or own individual “Self”.Personal egocentrism can manifest itself in humanbehavior, manner of reasoning, semantics of languagein the form of egotism and retroflexion. In ourwork we define egotism as a person’s desire to talkabout him/herself, to remember personal advantagesover others, thereby increasing his/her ownsignificance. Through egotism there is a self-presentationof one’s “Self”. Conclusions. It was found thatpupils of the first and second form show a high levelof egotism, and third and fourth -form pupils showedan average one. That is, at the end of primary schoolage the desire to talk only about oneself, to presentto the interlocutor only one’s own person decreases.With age and the acquisition of socio-psychologicalcompetence, there is a tendency to reduce selfishnessin primary school age as the desire of students topresent their own person during a conversation witha communication partner. The control of the egotisticallanguage and display of interest of the person actingas the partner on communication is shown. Thedominant form of personal egocentrism of a juniorschoolchild is the extroverted form.
Keywords: dialogic speech, egotism, junior school child, extroverted form, introverted form, personal egocentrism, retroflexion, communication